Hubungan Penggunaan Gadget dengan Risiko Gangguan Pemusatan Perhatian Hiperaktivitas dan Masalah Perilaku Emosional pada Anak Usia Dini - Armina, Armina (Universitas Baiturrahim, 2024)
Continuous use of gadgets in early childhood will have a negative impact on children's behavior patterns in their daily lives, such as children having more fun playing with gadgets than interacting with the surrounding environment. Early childhood is the golden age so it is easy to imitate whatever parents give them, therefore parents need to pay attention to their children's use of gadgets. Parents need to understand the influence of gadgets so that they do not have a negative impact on early childhood development. This shows that children's use of gadgets disrupts one aspect of children's development. This research aims to determine the relationship between gadgets with ADHD and MPE. This study used a cross sectional design with a population of all children aged 36-72 months in 3 kindergartens in Kenali Besar, namely 109 children with a sample size of 58 children using accidental sampling technique. Standard questionnaires and instruments for Attention Deficit Hyperactivity Disorder (ADHD) and Emotional Behavior Problems (MME). The research results were analyzed using the Chi Square Test. The results show that the maximum duration of children using gadgets is 31-120 minutes, there is no significant relationship between the duration of gadget use for children aged 36-72 months with ADHD and MPE.